Identification of microRNAs associated with the exogenous spermidine-mediated improvement of high-temperature tolerance in cucumber seedlings (Cucumis sativus L.) - Ying Wang (BMC Genomics, 2018)
Abstract Background High-temperature stress inhibited the growth of cucumber seedlings. Foliar spraying of 1.0 mmol·L− 1 exogenous spermidine (Spd) to the sensitive cucumber cultivar ‘Jinchun No. 2’ grown at high-temperature (42 °C/32 °C) in an artificial climate box improved the high-temperature tolerance. Although there have been many reports on the response of microRNAs (miRNAs) to high-temperature stress, the mechanism by which exogenous Spd may mitigate the damage of high-temperature stress through miRNA-mediated regulation has not been studied. Results To elucidate the regulation of miRNAs in response to exogenous Spd-mediated improvement of high-temperature tolerance, four small RNA libraries were constructed from cucumber leaves and sequenced: untreated-control (CW), Spd-treated (CS), high-temperature stress (HW), and Spd-treated and high-temperature stress (HS). As a result, 107 known miRNAs and 79 novel miRNAs were identified. Eight common differentially expressed miRNAs (miR156d-3p, miR170-5p, miR2275-5p, miR394a, miR479b, miR5077, miR5222 and miR6475) were observed in CS/CW, HW/CW, HS/CW and HS/HW comparison pairs, which were the first set of miRNAs that responded to not only high-temperature stress but also exogenous Spd in cucumber seedlings. Five of the eight miRNAs were predicted to target 107 potential genes. Gene function and pathway analyses highlighted the integral role that these miRNAs and target genes probably play in the improvement of the high-temperature tolerance of cucumber seedlings through exogenous Spd application. Conclusions Our study identified the first set of miRNAs associated with the exogenous Spd-mediated improvement of high-temperature tolerance in cucumber seedlings. The results could help to promote further studies on the complex molecular mechanisms underlying high-temperature tolerance in cucumber and provide a theoretical basis for the high-quality and efficient cultivation of cucumber with high-temperature resistance.